USE OF ELECTRONIC DEVICES AND ITS RELATIONSHIP WITH CERVICALGIA AND HEADACHE IN MEDICINE PROFESSORS AT A PRIVATE INSTITUTION IN ANÁPOLIS (CIPEEX, 2025)
Objective: To analyze the prevalence of cervicalgia and headaches related to screen use among professors in the Medicine program at a private university in Anápolis-GO. Method: This is an exploratory study that used Google Forms questionnaires for data collection. The sample was randomly composed of professors who voluntarily agreed to participate and signed the Informed Consent Form (ICF). The instruments used were the Sociodemographic Questionnaire, the Neck Disability Index (NDI), the Copenhagen Neck Functional Disability Scale, and a screen time questionnaire based on a study by Ruthes et al. (2020). Data analysis was performed using tables and graphs in Microsoft Excel 2013. Results: Most of the participating professors are female, with an average age of 45.1 years and 14.7 years of experience. Of the total, 57.1% presented mild disability according to the Copenhagen Neck Functional Disability Scale, and 51.56% had minimal disability according to the NDI. Additionally, 81.3% use screens before going to bed and 59.4% continue after lying down, although 75% are aware of the potential harm. About 57.8% reported feeling tired upon waking. Conclusion: Most professors show minimal to mild disability related to prolonged screen use, which may contribute to cervicalgia and headaches. Despite being aware of the negative effects, many continue using electronic devices before and after sleeping, which may contribute to morning fatigue.
Keywords: Headache; Cervicalgia; Screen time; Teaching